2012
DOI: 10.1177/2049463712439132
|View full text |Cite
|
Sign up to set email alerts
|

Opioids, pain and addiction – practical strategies

Abstract: 1. Addiction can occur with the repeated exposure of a biogenetically predisposed person to an addictive substance or behaviour. 2. In the patient with pain on opioid therapy, use the '4 Cs' to diagnose addiction. 3. Screening and risk stratification of all patients considered for opioid therapy is a key element of 'universal precautions' in pain management. 4. There are a number of established and new screening tools including the CAGE, Opioid Risk Tool and Screener and Opioid Assessment for Patients with Pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…After obtaining written, informed consent, the patients received a patient’s booklet and responded to the following questionnaires and forms: (1) Cut down, Annoyed, Guilty, Eye-opener Adapted to Include Drugs (CAGE-AID) [ 30 ]; (2) Brief Pain Inventory-Short Form (BPI-SF) [ 31 ]; (3) Pain Catastrophizing Scale (PCS) [ 32 ]; (4) Hospital Anxiety and Depression Scale (HADS) [ 33 ]; (5) Insomnia Severity Index (ISI) [ 34 ]; (6) Korean Instrumental Activities of Daily Living Scale (K-IADL) [ 35 ]; (7) Korean Connor-Davidson Resilience Scale (K-CD-RISC) [ 36 ]; and (8) Patient Global Impression of Change Scale (PGIC) [ 37 ]. Among the four questions in the CAGE-AID, one or more affirmative answers was considered “positive” for OUD [ 38 ]. BPI-SF measured pain intensity (Items 3–6) and pain interference (Item 9) [ 39 ], which had seven components scored from 0 (no interference) to 10 (interferes completely).…”
Section: Methodsmentioning
confidence: 99%
“…After obtaining written, informed consent, the patients received a patient’s booklet and responded to the following questionnaires and forms: (1) Cut down, Annoyed, Guilty, Eye-opener Adapted to Include Drugs (CAGE-AID) [ 30 ]; (2) Brief Pain Inventory-Short Form (BPI-SF) [ 31 ]; (3) Pain Catastrophizing Scale (PCS) [ 32 ]; (4) Hospital Anxiety and Depression Scale (HADS) [ 33 ]; (5) Insomnia Severity Index (ISI) [ 34 ]; (6) Korean Instrumental Activities of Daily Living Scale (K-IADL) [ 35 ]; (7) Korean Connor-Davidson Resilience Scale (K-CD-RISC) [ 36 ]; and (8) Patient Global Impression of Change Scale (PGIC) [ 37 ]. Among the four questions in the CAGE-AID, one or more affirmative answers was considered “positive” for OUD [ 38 ]. BPI-SF measured pain intensity (Items 3–6) and pain interference (Item 9) [ 39 ], which had seven components scored from 0 (no interference) to 10 (interferes completely).…”
Section: Methodsmentioning
confidence: 99%
“…Identifying patients at high risk of opioid abuse or dependence can help reduce adverse outcomes. 23 Despite this, only four hospitals in the present study reported including this strategy in their guideline. Screening for key indicators in the patient's history, including family history and psychological makeup, can determine whether the patient has an increased risk of developing a dependence to opioids.…”
Section: Discussionmentioning
confidence: 73%
“…Identifying patients at high risk of opioid abuse or dependence can help reduce adverse outcomes . Despite this, only four hospitals in the present study reported including this strategy in their guideline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some situations, oncologists may continue to prescribe opioids but with more discussions of limits and aggressive treatment of nonpain symptoms . Signs of an opioid use disorder (OUD) include the four C's: loss of c ontrol over use, a c ompulsion to continue to use, c ravings for the substance, and use despite negative c onsequences . Many patients with cancer have a degree of difficulty controlling their opioid use and may have a mild OUD in addition to cancer‐related pain; other patients may have a more severe OUD, making it unsafe to prescribe opioids at all.…”
Section: Introductionmentioning
confidence: 99%